Corporate Social Responsibility Initiatives For Childrens’ Education In The Rural Areas: A Case Study Of Adopt-A-School (ASC) Program From Pintar Foundation - Azhar, Athirah (2018)
Corporate Social Responsibility (CSR) initiatives has been actively conducting educational programmes under PINTAR Foundation since 2007 specifically in the rural and underserved areas in Malaysia. The primary objectives of this study are to examine the children perception about educational programmes under the CSR initiatives; to analyse the impact of educational programmes for the rural school academic performance and corporate company’s goal; and to recommend the interventions plans for the corporate companies CSR and school to further improve children’s educational programmes specifically in the rural schools. This qualitative study has chosen the ASC Program in PINTAR Foundation as a case study.